Physico-chemical Properties and Microbiological Composition of Optimised Tempeh and Milk Kefir - Nyuk L. Chin (Chemical Engineering Transactions, 2025)
The fermentation process of two selected fermented foods, tempeh and milk kefir are commonly performed at small scale in homes as part of healthy diet following local culture practise. Due to much variations in every fermentation process, the changes in physico-chemical and microbiological properties were studied and compared with commercial products. The fermentation parameters including temperature, time and humidity were optimised for desired product qualities using Response Surface Methodology (RSM) following the three factors Box Behnken design (BBD) for tempeh and two factors central composite design (CCD) for milk kefir. The optimised processing conditions for tempeh was 33.1 °C for 34.1 hours at 60 % relative humidity while for milk kefir was 35.8 °C for 8.8 hours. It was found that both optimised tempeh and milk kefir had significantly greater counts of lactic acid bacteria, aerobic plate counts and mold or yeast. Amplicon sequencing results have identified beneficial microbes that are probiotic including high abundance of Bacillus and Weisella in optimised tempeh while milk kefir contained mostly Lactobacillus and Streptococcus.